2015
DOI: 10.1016/j.surfcoat.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Towards smart electrolytic plasma technologies: An overview of methodological approaches to process modelling

Abstract: Article:Parfenov, E.V., Yerokhin, A., Nevyantseva, R. ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(59 citation statements)
references
References 103 publications
1
49
0
3
Order By: Relevance
“…If this process has undeniable assets for surface treatments of light alloys (high growth rate, high ultimate coating thickness, ecofriendliness, wear and corrosion resistance, etc. ), the high energy consumption and the lack of understanding of the fundamental processes underlying the breakdown and the oxidation mechanisms still limit a larger scale development.Improving the energetic efficiency of PEO is a major stake and several strategies can then be followed: dual treatments[1], addition of nanoparticles [2,3], electrolyte composition [4,5] and electric regimes [5][6][7][8]. Here, we focus on the influence of the electric regime as it has a direct and strong influence on both the space and time properties of micro-discharges (MD), which affect the coating growth.…”
mentioning
confidence: 99%
“…If this process has undeniable assets for surface treatments of light alloys (high growth rate, high ultimate coating thickness, ecofriendliness, wear and corrosion resistance, etc. ), the high energy consumption and the lack of understanding of the fundamental processes underlying the breakdown and the oxidation mechanisms still limit a larger scale development.Improving the energetic efficiency of PEO is a major stake and several strategies can then be followed: dual treatments[1], addition of nanoparticles [2,3], electrolyte composition [4,5] and electric regimes [5][6][7][8]. Here, we focus on the influence of the electric regime as it has a direct and strong influence on both the space and time properties of micro-discharges (MD), which affect the coating growth.…”
mentioning
confidence: 99%
“…Parfenov et al [2] summarized plasma electrolytic technology and proposed a theoretical model that can be used for further observing the reaction process in this technology. Plasma electrolytic oxidation is usually used for metal oxidation and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The formation different kind of oxide layers has been achieved by the anodic oxidation and plasma surface treatment in the sparking regime (plasma electrolytic oxidizing PEO) seems to be the very promising since it does not need the sophisticated facilities, allows to form various types of titania and to incorporate different species into the layer by modification of electrochemical parameters and of electrolyte chemistry [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time it was found that, in most cases, catalyst materials based on mixed two or three component oxide systems exhibit high activity and selectivity not only in heterogeneous red-ox reactions [3-5] but also in photo-catalytic ones [6][7][8]. Synthesis of nano-composite catalytic disperse systems based on titania is carried out by various methods, including sol-gel processes [6,9,10].The formation different kind of oxide layers has been achieved by the anodic oxidation and plasma surface treatment in the sparking regime (plasma electrolytic oxidizing PEO) seems to be the very promising since it does not need the sophisticated facilities, allows to form various types of titania and to incorporate different species into the layer by modification of electrochemical parameters and of electrolyte chemistry [11][12][13][14].Titania layers containing manganese oxides obtained by PEO in acetate-borate electrolyte was noted to be catalytic active in CO conversion to CO 2 [15]. Cobalt-containing oxide coatings on titanium are obtained from a silicate electrolyte with cobalt acetate addition [16].…”
mentioning
confidence: 99%